1997
DOI: 10.1074/jbc.272.25.15980
|View full text |Cite
|
Sign up to set email alerts
|

Synaptojanin Inhibition of Phospholipase D Activity by Hydrolysis of Phosphatidylinositol 4,5-Bisphosphate

Abstract: A 150-kDa protein that inhibits phospholipase D (PLD) activity stimulated by ADP-ribosylation factor and phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ) was previously purified from rat brain. The sequences of peptides derived from the purified PLD inhibitor now identify it as synaptojanin, a nerve terminal protein that has been implicated in the endocytosis of fused synaptic vesicles and shown to be a member of the inositol polyphosphate 5-phosphatase family. Further characterization of the enzymatic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 31 publications
0
84
0
Order By: Relevance
“…Such degradation is likely to be catalyzed to a significant extent by synaptojanin 1, a major polyphosphoinositide phosphatase in brain. Synaptojanin 1 dephosphorylates PtdIns(4,5)P 2 and PtdIns (4)P via its inositol 5-phosphatase domain and Sac1 domain, respectively (16,17,46,47). It therefore is thought to represent a negative regulator of membrane-clathrin coat interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such degradation is likely to be catalyzed to a significant extent by synaptojanin 1, a major polyphosphoinositide phosphatase in brain. Synaptojanin 1 dephosphorylates PtdIns(4,5)P 2 and PtdIns (4)P via its inositol 5-phosphatase domain and Sac1 domain, respectively (16,17,46,47). It therefore is thought to represent a negative regulator of membrane-clathrin coat interactions.…”
Section: Discussionmentioning
confidence: 99%
“…PLD is inhibited by endocytic proteins such as synaptojanin, AP180, and amphiphysin. Although AP180 and amphiphysin directly interact with PLD (50,51), the inhibition of PLD by synaptojanin is attributed to its ability to dephosphorylate PtdIns(4,5)P 2 (20,46), which is a cofactor for PLD (51).…”
Section: Discussionmentioning
confidence: 99%
“…One group of these enzymes contains only a NH 2 -terminal Sac domain, and the second class contains an additional, 5-phosphatase domain in the center of the protein followed by various other domains (155). Sac1p was identified in a screen for mutations that relieved the block in secretion caused by loss of activity of the S. cerevisiae PITP, Sec14p (51,385), and was subsequently discovered to have PIP phosphatase activity (47,124). In S. cerevisiae there are two such proteins, Sac1p and Fig4p, and in humans three, KIAA0274, KIAA0966, and KIAA0851.…”
Section: Sac Family Phosphatasesmentioning
confidence: 99%
“…However, it is unknown whether these events occur at a pre-or postsynaptic location. Furthermore, the potential control of PLD at a presynaptic location would be of particular interest as it has recently been reported that synucleins (Jenco et al, 1998) and synaptojanin (Chung et al, 1997), proteins located abundantly at the presynaptic terminal, can act as endogenous PLD inhibitors, implying that PLD action at the presynaptic terminal is physiologically signi®cant. The aim of our study was to examine the signal transduction pathway which links mGluRs to PLD in our presynaptic-rich rat cerebrocortical synaptosome preparation and to determine whether PKC activation, occurring secondary to PLC activation, is involved in the activation process.…”
Section: Introductionmentioning
confidence: 99%